(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Survival of Small and medium scale enterprises (SMEs) are integral to economic growth and development. Not only do they contribute in the GDP growth and employment creation but are the engine of most market driven economies. The identification and recalibration of the catalyst of this very important economic issue and subject is topical in contemporary discourse on the issues of national growth and development. Consequent on its importance, lot of scholarly works have been advanced with several postulations and suggestions from and within different context. This study however adopted a some-worth divergent view since it approach the subject of survival of SMEs from the Entrepreneurial capacity perspective. The position and line of thought within the context of the subject matter is that if there is an activation and engagement of entrepreneurial capacity measured by innovativeness, risk taking and pro-activeness, there will be a high chance of the survival of SMEs in Nigeria. Survival of SMEs was measured by adaptability, flexibility and improved customer service. The predictor and criterion variables was examined within the context of technology, thus, technology was the moderating variable. To put the work in context and to give it a direction, ten null hypotheses were structured from the reviewed literature. The hypotheses were tested using structural equation modelling through the AMOS package. From the test, results and findings were made upon which we made some recommendations.